2015
DOI: 10.1513/annalsats.201408-391oc
|View full text |Cite
|
Sign up to set email alerts
|

Lansoprazole Is Associated with Worsening Asthma Control in Children with the CYP2C19 Poor Metabolizer Phenotype

Abstract: Children with the PM phenotype developed worse asthma control after 6 months of lansoprazole treatment for poorly controlled asthma. Increased exposure to proton pump inhibitor may worsen asthma control by altering responses to respiratory infections. Clinical trial registered with www.clinicaltrials.gov (NCT00604851).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
4

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 41 publications
0
19
0
4
Order By: Relevance
“…Another study by Lang et al [98] investigated the association between CYP2C19 genotype and asthma control (assessed by Asthma Control Questionnaire (ACQ)) in pediatric patients who were classified as IM/PM or NM and were treated with lansoprazole. At 6 months, IM/PM phenotype was associated with worsened asthma as compared to NM phenotype (+0.16 vs. −0.13; p  =  0.02) and placebo (+0.16 vs. −0.23; p  < 0.01) at 6 months.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…Another study by Lang et al [98] investigated the association between CYP2C19 genotype and asthma control (assessed by Asthma Control Questionnaire (ACQ)) in pediatric patients who were classified as IM/PM or NM and were treated with lansoprazole. At 6 months, IM/PM phenotype was associated with worsened asthma as compared to NM phenotype (+0.16 vs. −0.13; p  =  0.02) and placebo (+0.16 vs. −0.23; p  < 0.01) at 6 months.…”
Section: Cyp2c19 and Ppi Pharmacogeneticsmentioning
confidence: 99%
“…In a subsequent genetic sub-study, we showed that participants with IM or PM had significantly higher lansoprazole levels compared to NM and were significantly more likely to suffer respiratory adverse events related to URI and strep/sore throat [64]. These same PM participants developed worse asthma controlled (triggered by URI) compared to NM after 4 months on conventional PPI dosing [71]. Conventional dosing of PPI in these IM and PM patients is likely to improve GERD symptoms at the cost of greater risk of URIs.…”
Section: Discussionmentioning
confidence: 84%
“…We appreciate the interest of Dr. Sukhovershin, Dr. Ghebremariam, and Dr. Cooke in our recent report about worsening asthma control among children taking lansoprazole who have the CYP2C19 poor metabolizer phenotype (1). The authors correctly point out that we found that these children developed worse asthma symptoms after 5 months of lansoprazole therapy.…”
Section: From the Authorsmentioning
confidence: 75%
“…I read with great interest the study "Vigorous exercise can cause abnormal pulmonary function in healthy adolescents," recently published by Abosaida and colleagues (1).…”
Section: Fev 1 Can Be Associated With Reduced Values After Vigorous Ementioning
confidence: 99%